2023
DOI: 10.1002/ags3.12694
|View full text |Cite
|
Sign up to set email alerts
|

Robotic‐assisted colectomy for right‐sided colon cancer: Short‐term surgical outcomes of a multi‐institutional prospective cohort study in Japan

Abstract: BackgroundIn Japan, there are no substantial reports on robotic‐assisted colectomy because few institutions performed the procedure, as it was not covered by national insurance until March 2022.AimThis study aimed to evaluate the safety and feasibility of robotic‐assisted colectomy for patients with curatively resectable colon cancer in Japan.MethodsThis multi‐institutional, prospective, single‐arm, observational study enrolled patients diagnosed with curatively resectable clinical stage I–IIIC colon adenocarc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…28 There has been only one report in Japan to date, showing Clavien-Dindo grade II or higher morbidity of 11%, grade III morbidity of 4% and no mortality after Ro-RC for right-sided colon cancer. 11 In this study, the morbidity of Clavien-Dindo grade II or higher was 7.6%, grade III was 0%, and there was no mortality, similar to previously reported results.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…28 There has been only one report in Japan to date, showing Clavien-Dindo grade II or higher morbidity of 11%, grade III morbidity of 4% and no mortality after Ro-RC for right-sided colon cancer. 11 In this study, the morbidity of Clavien-Dindo grade II or higher was 7.6%, grade III was 0%, and there was no mortality, similar to previously reported results.…”
Section: Discussionsupporting
confidence: 91%
“…Currently, Ro-RC is gradually expanding in Japan, but only one prospective clinical trial has been reported to date. 11 In this prospective phase II study, we evaluated the safety of Ro-RC in the introduction phase.…”
Section: Introductionmentioning
confidence: 99%
“…However, robotic surgery has been reported to prolong the operative time in comparison to laparoscopic surgery 1 . In particular, robotic surgery for colon cancer has been reported to be non‐inferior to laparoscopic surgery in terms of the open conversion rate 8 . The benefits of robotic surgery may be fully realized in cases with vascular anomalies, such as in the present case.…”
Section: Discussionmentioning
confidence: 65%
“…The use of robot‐assisted surgery for colon cancer is increasing. Outcomes of robotic surgery for colon cancer are reportedly comparable to those of laparoscopy 1,7,8 . Laparoscopic surgery is the most commonly performed surgery for colorectal cancer.…”
Section: Discussionmentioning
confidence: 96%
“…In Japan, robotic surgery for rectal resection was covered by insurance in 2018, whereas that for colon cancer surgery was covered in 2022, and such coverage is expected to spread to other medical conditions with the increasing societal need for minimally invasive surgery. In Japan, a prospective cohort study on robotic surgery for colon cancer demonstrated the safety and curative potential of the surgical system [ 3 ]. The world's first minimally invasive single-incision laparoscopic surgery (SLS) was reported in 2008 [ 4 ], and many studies have shown its safety and favorable oncologic outcomes compared with those of multiport laparoscopic surgery [ 5 8 ].…”
Section: Introductionmentioning
confidence: 99%